The effect of a single dose of intravenous tranexamic acid on visual clarity in knee arthroscopic meniscectomy without a tourniquet: Tranexamic acid in knee arthroscopic meniscectomy - Çataltepe, Aziz; Öznam , Kadir (Journal of Surgery and Medicine, 2023)
Background/Aim: Tranexamic acid (TXA) is known to reduce intra-articular bleeding during arthroscopic procedures, which can improve visibility and reduce postoperative pain and knee joint swelling from hemarthrosis. However, insufficient data supports the routine use of TXA in arthroscopic meniscectomy. This study aimed to evaluate the effect of a single dose of intravenous (IV) TXA on visual clarity in arthroscopic meniscectomy without a tourniquet. Methods: A randomized, double-blind, controlled trial was conducted to assess the use of TXA for visibility in routine arthroscopic meniscectomy without a tourniquet. Between January 2021 and February 2022, 53 patients undergoing arthroscopic meniscectomy were randomly assigned to either the TXA group (n=27), who received 1 g IV-TXA, or the control group (n=26), who received 100 ml of normal saline. Visual clarity was evaluated using a Numeric Rating Scale (NRS). Patients were also assessed for the need for a tourniquet, tourniquet time, total operative time, volume of irrigation fluid, postoperative pain, hemarthrosis, and knee function on postoperative day 3 and weeks 1, 2, and 4, using the Lysholm knee scoring scale. Results: There was no significant difference in intra-operative arthroscopic visibility between the TXA and control groups (P=0.394). Tourniquet was required in three cases in the TXA group and four cases in the control group (P=0.646). There was no significant difference between the two groups regarding postoperative pain, grade of postoperative hemarthrosis, knee motion, or the Lysholm Knee Score after the operation. Conclusion: The administration of IV-TXA in arthroscopic meniscectomy without a tourniquet did not provide any benefits such as enhanced surgical visualization, reduction in the need to inflate the tourniquet due to obstructed visibility, or decrease in hemarthrosis, VAS pain score, or improved range of motion of the knee in the postoperative period when compared to the control group.